FUNCTIONAL PERFORMANCE INDICATORS DURING SYSTEMS DEVELOPMENT TO PROTECT INFORMATION FROM UNAUTHORISED ACCESS - G. I. Kachaeva; A. D. Popov; E. A. Rogozin (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Objectives. In order to investigate the property of the operational effectiveness of automated systems for protecting information from unauthorised access, it is necessary to analyse the normative documents (both international and Russian) and scientific materials devoted to the evaluation of software quality. The aim of the study consists in the analysis of the existing deficiencies in systems for protecting information from unauthorised access, on the basis of which analysis it is possible to develop performance indicators, substantiate and develop the criteria for assessing the operational effectiveness of the information protection systems from unauthorised access in automated information systems  and develop an algorithm for the integrated evaluation of the operational effectiveness of information protection systems on the basis of the established criteria and indicators.Methods. One of the methods for solving the set goals consists in the main provisions of efficiency and systems theories, which in turn became the theoretical basis for solving problems involved in the creation of criteria and assessment of performance indicators of information protection systems.Results. The criteria and performance indicators for the creation of automated information systems are developed on the basis of the analysis of open literature sources and existing shortcomings in the real use of systems for protecting information from unauthorised access. An algorithm for the integrated evaluation of the operational effectiveness of the information protection systems is developed.Conclusion. In the article, based on the analysis of normative documents (both international and Russian), as well as on the scientific materials devoted to the quality (function efficiency) of complex software systems, to which the information protection systems can be related, a system of performance indicators was developed. These can be indicators can be classified as partial (static, practically independent of time, the evaluation of which is based on expert estimates) and integral (dynamic, time-dependent, the evaluation of which is based on mathematical modeling).